Interaction Between Beauveria bassiana (Hypocreales: Cordycipitaceae) and Coptera haywardi (Hymenoptera: Diapriidae) for the Management of Anastrepha obliqua (Diptera: Tephritidae). Issue 2 (14th March 2020) - Martínez-Barrera, Olga Yaneth; Toledo, Jorge; Cancino, Jorge; Liedo, Pablo; Gómez, Jaime; Valle-Mora, Javier; Montoya, Pablo
Abstract: The interaction between the entomopathogenic fungus Beauveria bassiana (Balsamo) and the parasitoid Coptera haywardi (Oglobin), as potential biological control agents for Anastrepha obliqua (Macquart) fruit flies, was evaluated under laboratory and semi-protected field cage conditions. The effects of the parasitoids and fungus were individually and jointly assessed in Plexiglas cages. Application of B. bassiana dry conidia to soil produced 40% mortality in A. obliqua adults. However, mortality was lower (21.2%) on evaluation under field cage conditions. According to the multiple decrement life table analysis, the probability of death of A. obliqua was 88% when C. haywardi parasitoids and B. bassiana conidia were used in conjunction, 89% when only C. haywardi parasitoids were released and 23% when only B. bassiana conidia were applied. These results demonstrate that no synergistic, additive or antagonistic interaction took place with the simultaneous use of these natural enemies, since the presence of B. bassiana had no effect on the C. haywardi parasitism. These results indicate that the parasitoid is a better natural enemy for the control of A. obliqua, and show that, although the two biological control agents can be used simultaneously, their joint application will not produce increased control.